Holocene sea levels in Southeast Asia, Maldives, India and Sri Lanka: The SEAMIS database. (1st September 2019) - Mann, Thomas; Bender, Maren; Lorscheid, Thomas; Stocchi, Paolo; Vacchi, Matteo; Switzer, Adam D.; Rovere, Alessio
Abstract: We assembled a database of Holocene relative sea-level index points (n = 213) and marine (n = 211) and terrestrial (n = 122) limiting points for the broader South and Southeast Asian region including the Maldives, India and Sri Lanka. The standardized review of published age-elevation information from corals, deltaic, estuarine and mangrove deposits, beachrocks and tidal notches, yielded a new suite of relative sea-level index and limiting points produced according to a standardized protocol. Expected spatial variability in Holocene relative sea-level change due to glacial isostatic adjustment was accounted for, by first subdividing the study area into ten geographic sub-regions from the Central Indian Ocean to the Western Tropical Pacific, and second by comparing sub-regional relative sea-level data to model predictions of glacial isostatic adjustment. Results show that some of the regionally constrained relative sea-level data are characterized by significant inconsistencies that cannot be explained by glacial isostatic adjustment. Such inconsistencies of standardized relative sea-level data become particularly obvious in areas around the Red River Delta in Vietnam, the Gulf of Thailand, the northwest coast of Malaysia and the Spermonde Archipelago in Indonesia. Based on a critical evaluation of the reviewed relative sea-level indicators, we discuss possible sources of local divergence and identify regions where data are currently insufficient to constrain glacial isostatic adjustment predictions. The remaining quality-controlled and consistent relative sea-level data show that glacial isostatic adjustment and syn-/post-formational influences such as tectonic uplift, subsidence and compaction were the dominant local drivers of Holocene relative sea-level change. Collectively, the results of this review suggest that Holocene sea levels in South and Southeast Asia and surrounding regions have been controlled by a variety of global and local drivers and imply that additional index points from the Java Sea in Indonesia would be valuable to better assess the spatial variability, and to calibrate geophysical models of glacial isostatic adjustment. Highlights: A database of 546 standardized Holocene relative sea-level indicators for South and Southeast Asia is presented. Results show that the study areas experienced RSL histories of considerable variance. The main drivers of Holocene relative sea-level change are glacial isostatic adjustment, tectonic uplift and subsidence. Continental levering is one dominant driver of the spatial variability in the magnitudes of relative sea-level highstands.